THE SOLUBILITY OF AU-AG ALLOY + AGCL IN HCL/NACL SOLUTIONS AT 300°C: NEW DATA ON THE STABILITY OF AU(I) CHLORIDE COMPLEXES IN HYDROTHERMAL FLUIDS - Gammons C.H.; Williams-Jones A.E. (My University, 1995)
The solubility of Au-Ag alloy (electrum) + AgCl (chlorargyrite) was measured in aqueousHCl solutions at 300°C. Equilibrium between the two solid phases provided a convenient and highly effective fo2 sensor. By varying the initial electrum composition (XAu = 0.3 to 1.0), total chloride concentration (0.1 to 5.0 molal), and pH (HCl = 0.003 to 1.0), it was possible to survey a wide range in oxidation state (log fo2 = -13.3 to -35.1). High metal solubilities were measured under these conditions (0.3 to >3000 ppm Au; 1280 to >40,000 ppm Ag). All evidence indicates that Au dissolved as an aurous (+I) chloride complex at 300°C. This species subsequently disproportionated to a mixture of auric (+III) species and metallic Au upon cooling to room temperature.The solubility data were used to determine equilibrium constants for the following reactions: The value of log K for (A2) is in excellent agreement with previous studies (Seward, 1976; Zotov et al., 1986a,b), whereas the value for (A1) is consistent with the data of Nikolaeva et al. (1972), Helgeson (1969), and Zotov et al. (1991), but not with the results of Henley (1973) and Wood et al. (1987). The log K for (A3) is the first direct determination of a distribution coefficient for exchange of Au and Ag between solid solution and aqueous solution.The above data were combined with results from previous experimental studies to compile a complete set of log K values for reactions (A1), (A2), and (A3) in the temperature range 25 to 350°C. Silver is far more soluble than Au as a chloride complex throughout this temperature range. Nonetheless, AuCl2 may be an important agent for Au transport at T > 300°C, or in highly oxidized (e.g., surface-derived) fluids. Because of the very strong thermodynamic force for Ag to partition into the aqueous phase (reaction A3), Au-Ag alloys in equilibrium with Cl-rich and S-poor fluids will tend to be Au-rich, especially at lower temperature.